Limiar de lactato sanguíneo durante exercício resistido dinâmico em mulher hipertensa e diabética - Cruz, Angélica Cristiane da [UNESP] (2015)
Introduction: The anaerobic threshold (AT), metabolic transition point of great importance for aerobic exercise prescription, has recently been investigated during resistance exercise (OLIVERA, 2006). Increased sympathetic activity in response to the increased intensity of exercise stimulates the production of catecholamines, resulting in increased blood glucose levels and consequently lactate (Cavalcanti et al 2010), whose blood concentration is stable until the anaerobic threshold (AT) , at which production exceeds the body's ability to remove (Wasserman et al, 1973). Above the AT metabolic stress is higher which in turn increases cardiac and respiratory distress Method: Was studied a woman to 55 years, hypertensive and diabetic. Voluntary performed 20 repetitions for one minute with 10% load obtained in the 1RM test and after stopping test blood was collected on the earlobe for lactate analysis. This same procedure was performed in series with subsequent increase of 10% in 10% of the maximum load to that observed up to the value correspondent fixed 4 mMol.L lactate, which was considered as the lactate threshold (DENADAI, 1995; HECK et al,1985). Objective: To identify the intensity occurring anaerobic threshold during resistance exercise knee extension in a woman with laughing factors for cardiovascular disease. Results and discussion: There was loss of linearity of lactate concentration and exceeded 4 mMol.L intensity of 30%, which corroborates other studies that indicate that the anaerobic threshold is between 30% and 40% of 1 RM. Conclusion: According to our results we can conclude that anaerobic threshold during resistance exercise rushed intensity of 30% of the maximum strength of a woman aged 55 years, diabetic and hypertensive on optimal medication.